2017
DOI: 10.1186/s13059-017-1270-7
|View full text |Cite
|
Sign up to set email alerts
|

Population and allelic variation of A-to-I RNA editing in human transcriptomes

Abstract: BackgroundA-to-I RNA editing is an important step in RNA processing in which specific adenosines in some RNA molecules are post-transcriptionally modified to inosines. RNA editing has emerged as a widespread mechanism for generating transcriptome diversity. However, there remain significant knowledge gaps about the variation and function of RNA editing.ResultsIn order to determine the influence of genetic variation on A-to-I RNA editing, we integrate genomic and transcriptomic data from 445 human lymphoblastoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 78 publications
5
45
0
Order By: Relevance
“…To provide a quantitative assessment of editing in a larger population of animals, the base composition of candidate sites identified in the nine 'discovery' animals was assessed in 355 additional animals for which RNAseq data was available. The proportion of reads edited in these 'quantification' animals was defined as phi (Φ; (Park et al, 2017)). Phi values varied widely across sites: from 0.03% to 90.04% for A-to-I reads (median 12.81, mean 17.89).…”
Section: Proportions Of Reads Editedmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide a quantitative assessment of editing in a larger population of animals, the base composition of candidate sites identified in the nine 'discovery' animals was assessed in 355 additional animals for which RNAseq data was available. The proportion of reads edited in these 'quantification' animals was defined as phi (Φ; (Park et al, 2017)). Phi values varied widely across sites: from 0.03% to 90.04% for A-to-I reads (median 12.81, mean 17.89).…”
Section: Proportions Of Reads Editedmentioning
confidence: 99%
“…Since numerous regulatory effects have been attributed to RNA editing, genetic regulation of editing poses another potential mechanism to explain impacts on physiological traits. In three recent studies conducted in Drosophila (Ramaswami et al, 2015), mice (Gu et al, 2016), and humans (Park et al, 2017), researchers demonstrated the application of QTL mapping approaches to reveal widespread genetic modulation of RNA-editing. In the current study, we aimed to build on these studies by characterising the genetic landscape of RNA-editing in cattle, and more specifically, use these data to investigate potential regulatory effects of identified loci on gene expression and complex quantitative traits.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold for minimum RNA-sequencing reads is necessary for distinguishing SNV positions with monoallelic reference signal from non-expressed SNV positions and is critical for the estimation of VAFRNA. In the presented results, we have selected a threshold of 10 RNA-sequencing reads covering each SNV position of interest, based on considerations for sequencing depth and confidence of the VAFRNA assessment, and also following trends in the assessment of RNA editing from RNA-sequencing data (Park et al, 2017). Our experiments with various minimum thresholds show that higher thresholds increase the accuracy of the VAFRNA estimation, naturally retaining a lower number of variants for analysis (Movassagh et al, 2016).…”
Section: Reqtl Usagementioning
confidence: 99%
“…Editing can be enhanced or suppressed by deviations from perfect base-pairing (i.e., mismatches, bulges and loops), suggesting complex structural contributions to editing specificity [14][15][16] . The quantitative trait loci (QTL) mapping approach has been used to identify genetic variants associated with variability in RNA editing in Drosophila and humans, demonstrating that many editing QTLs (edQTL) can act through changes in the local and distal secondary structure for edited dsRNAs, consistent with importance of RNA structure 20,21 . Nevertheless, few general properties have emerged across different substrates, suggesting complex structural contributions to editing specificity 22 .…”
Section: Introductionmentioning
confidence: 99%